On the Implementation Time of Distributed Computing in Synchronous Mode with a Limited Number of Copies of a Software Resource - Pavlov, P. A. (Programming and computer software, 2025)
This paper constructs a mathematical model of distributed computing with a limited number of copies of a structured software resource. In the cases of unlimited and limited parallelism with respect to the number of processors in a multiprocessor distributed computing system, the problems of finding the minimum execution time of heterogeneous, homogeneous, and identically distributed competitive processes in synchronous mode, which ensures the continuous execution of each block of software resource by all processes, are solved.